African-American Identity in Toni Morrison’s Beloved (1987) - Khrisat, Abdulhafeth Ali (The Journal of US-Africa Studies, 2023)
This paper aims to examine the African-American identity in Toni Morrison’s Beloved (1987). The novel emphasizes the painful aspects of slavery such as sexual abuse and violence and explores the effects of the institution of slavery on the African-American character’s identity. The paper also addresses what it means to have a name and be free. The slavery institution does not believe in individuality. Naming is significant since it identifies the character. An analysis of the character’s identity and name will be studied since the characters have written their own stories and they are historically deprived of their humanity and language, a major constituent of the character’s personal and fellow slaves’ history. Therefore, the African-American character looks at the past as he/she longs for the sense of self. Moreover, the African slave is prohibited from being himself/herself or from belonging to a family. In this kind of institution, the African-American doubts the essential aspects of his identity, such as his value as an individual and the source of his manhood. Even after emancipation, the character feels that he has no identity, alienated and has no sense of self. After being freed, the characters try to reclaim their identities. The characters rename themselves in a way that they can now become ‘definer’ not ‘defined’: specific examples and references will be drawn from the narrative. The white founders of the institution of slavery commit acts of raping, an attack on one’s freedom, stealing and stripping the slave’s belongings and possessions, including his name. KeyWords: Morrison, Beloved, Identity, African-American Novel, Slavery.